2022
DOI: 10.1007/s40572-022-00364-6
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture Production and Value Chains in the COVID-19 Pandemic

Abstract: Purpose of Review The purpose of this review is to summarize the impacts of the coronavirus disease 2019 (COVID-19) pandemic on aquaculture input supply, production, distribution, and consumption. Recent Findings The COVID-19 pandemic–related lockdowns, social distancing, supply chain disruptions, and transport restrictions affect seafood production, distribution, marketing, and consumption. Recommendations are suggested to overcome these challenges. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 64 publications
(71 reference statements)
3
20
0
1
Order By: Relevance
“…Although the number of fish stocks increased due to reduced disturbance in fishing grounds, the pandemic could not bring societal benefits as all fisheries sub-sectors were affected differently [42]. FAO (2020) and Ben et al ( 2021) almost said the same for Bangladeshi fishers, as noted above [4,13]. In another study, Sunny et al (2021) indicated that this pandemic affected the Bangladeshi fishers' livelihoods in multiple ways, with sudden illness, reduced income, complications for starting production and input collection, labor crises, transportation abstraction, complexity in the food supply, a weak value chain, low consumer demand, rising commodity prices, and creditor pressure being the primary drivers [39].…”
Section: Impact #6: Livelihoodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the number of fish stocks increased due to reduced disturbance in fishing grounds, the pandemic could not bring societal benefits as all fisheries sub-sectors were affected differently [42]. FAO (2020) and Ben et al ( 2021) almost said the same for Bangladeshi fishers, as noted above [4,13]. In another study, Sunny et al (2021) indicated that this pandemic affected the Bangladeshi fishers' livelihoods in multiple ways, with sudden illness, reduced income, complications for starting production and input collection, labor crises, transportation abstraction, complexity in the food supply, a weak value chain, low consumer demand, rising commodity prices, and creditor pressure being the primary drivers [39].…”
Section: Impact #6: Livelihoodsmentioning
confidence: 97%
“…In such situations, non-governmental/governmental organizations in Bangladesh provided little to no support, further increasing the country's vulnerability to food insecurity [41]. However, certain fishers in Bangladesh adopted multilevel resilience strategies at the individual and household levels to cope with such situations, including diversifying their livelihood, creating more friendships, and networking among The COVID-19 pandemic also severely affected the global aquaculture supply chain by creating extended production delays (Figure 3) [4,13]. Additional problems faced in this sector included dilemmas regarding the transportation and selling of the final products at the market, shortage in production inputs, and difficulties obtaining credit from banks and other financial institutions, as reported for China [32].…”
Section: Impact #1: Fish Supply Chain Disruptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other paper report that the world tilapia production reached around 6 million tons in 2020, with a light grew (3.3 percent) than previous year, [2]. Despite the impact caused by the COVID-19 pandemic; China and Indonesia were the greatest producer in the world with1.8 million tons and 900,000 tons respectively in 2019 [3]. On the other hand, in 2010 the aquaculture production in Latin America, reached 1,883,134 tons, and the main producing countries were Chile (701,062 tons), Brazil (479,399 tons), Ecuador (271,919 tons), Mexico (126,240 tons), Peru (89,021 tons) and Colombia (80,367 tons) [4].…”
Section: Introductionmentioning
confidence: 99%